A laparoscopic resection of mucocele appendix in COVID time:a case report - Tanwar, Himanshu; Chawla, Subhash; Biswas, Prakash; Sharma, Shivam (International Surgery Journal, 2022)
We present a case of 62 year old female presented with complaints of pain right lower abdomen. Contrast enhanced computed tomography (CECT) abdomen showed appendicular lesion likely mucocele appendix. Diagnostic laparoscopy and proceed was planned. Intraoperatively there was no pathological condition found at the base of appendix and there were no lymph nodes enlarged so laparoscopic appendectomy was done carefully and specimen was retrieved in endo bag. Appendiceal mucocele is a rare disease and has a clinical picture that may resemble acute appendicitis. Mucocele of the appendix can also mimic an adnexal mass due to its nonspecific symptoms and prove to be a diagnostic challenge. A correct diagnosis before surgery is very important for the selection of surgical technique. Ultrasonography (USG) and CECT abdomen, should be used extensively for this purpose. Laparoscopic surgery provides the advantage of good exposure with more rapid recovery and a better cosmetic outcome provided that there should be no intraperitoneal spillage.